Cyclopiazonic acid suppresses the function of Leydig cells in prepubertal male rats by disrupting mitofusin 1-mediated mitochondrial function - Hang Lin; Ming Su; He Zhu; Yang Yu; Jianmin Sang; Yiyan Wang; Qiqi Zhu; Yang Zhu; Xiaoheng Li; Xingwang Li; Ren-Shan Ge; Huitao Li (Ecotoxicology and Environmental Safety)
This research investigated the impact of cyclopiazonic acid (CPA), a mycotoxin, on the function of progenitor Leydig cells (PLCs) in prepubertal male rats, focusing on its potential disruption of mitochondrial integrity through mitofusin 1 (MFN1) modulation. In vivo, Sprague Dawley rats received CPA (0.2, 1, 5 mg/kg/day) via gavage from postnatal days 21–28 to evaluate PLC function and mitochondrial morphology using serum hormone levels, histology, qPCR, and Western blot analyses. In vitro, rat R2C cells were treated with CPA (0.1, 1, 10 μM) alone or in combination with 100 μM leflunomide to assess PLC development through testosterone measurements, Western blotting, flow cytometry, and Mito-Tracker Green Staining. The findings from in vivo experiments showed that CPA reduced serum testosterone and progesterone levels at 1 mg/kg/day. The qPCR and Western blotting analyses revealed significant alterations in the expression of genes and proteins pertinent to PLC function, such as Scarb1, Star, Cyp11a1, and Cyp17a1. Immunofluorescence staining further revealed a reduction in MFN1 expression following exposure to CPA. In vitro experiments corroborated these observations, demonstrating that CPA induced mitochondrial fragmentation by downregulating SIRT1, PGC1-α, MFN1, and OPA1, increase reactive oxygen species, and inhibit testosterone synthesis in R2C cells. The administration of leflunomide was shown to mitigate the detrimental effects of CPA on PLCs. In conclusion, this research sheds new light on the deleterious effects of CPA on the reproductive development of prepubertal males.